Influência do tratamento clareador e envelhecimento induzido sobre o brilho, cor, dureza e rugosidade superficial de resinas compostas - Mathias, Ingrid Fernandes [UNESP] (2015)
Whitening procedures are frequent in esthetic dentistry. Resin composites undergo a certain amount of surface degradation of their organic matrix, resulting in possible decrease of mechanical and optic properties, and the long-term influences of this treatment on resin composite surface properties are still not known. The aim of the present study was to assess in vitro the influence of whitening therapy associated with induced aging on color, gloss, roughness and hardness of microparticled and nanoparticled resin composites. Material e Methods: One hundred and eighty specimens of each resin composite (Durafill VS - Heraeus Kulzer / Filtek Z350 XT - 3M ESPE, microparticled and nanoparticled resins, respectively) was fabricated with dimensions of 6 mm in diameter and 1 mm in thickness for gloss and color tests, 5 mm in diameter and 3 mm in thickness for microhardness tests, and 6 mm in diameter and 3 mm in thickness for roughness tests. Specimens was divided into three main groups: with no whitening therapy, with whitening therapy using 38 % hydrogen peroxide (Opalescence Boost – Ultradent), and with whitening therapy using 15 % carbamide peroxide (Opalescence PF 15 % - Ultradent). The main groups was further divided into two groups, one receiving inducing aging by light (Suntest CPS+ - Atlas) and the other water aging. One-third of each final group (n=10) had color and surface gloss assessed, the other third (n=10) for roughness, and the last third for hardness assessments. The parameters was assessed at baseline, after the whitening therapy (in case whitening was performed), and after the proposed aging therapy. Data was assessed for normality distribution and submitted to three-way ANOVA and multiple comparison tests. The level of significance was set at 5 %. Nanofilled resin suffered color change. The whitening procedures did not affect the gloss of resins and the aging by light significantly reduced this property. After aging, surface hardness increased, with higher values for aging in water. The roughness values increased after aging by light. We concluded that none of the whitening therapies could accelerate the process of degradation of resin composites, except carbamide peroxide on roughness samples.